(untitled) (Ustozlar uchun, 2025)
This article investigates the relationship between bilingual skills and English language achievement, focusing on how competence in two languages influences cognitive processing, academic performance, and linguistic development in English. Bilingual learners often develop enhanced metalinguistic awareness, stronger memory skills, and greater cognitive flexibility, which contribute positively to their English proficiency. However, bilingualism may also introduce challenges such as language interference, mixed structures, and imbalanced fluency across languages. This article analyzes the advantages and limitations that bilingual learners experience and highlights how bilingual skills, when supported through effective teaching strategies, can significantly improve English language achievement.